A metasomatized lithospheric mantle control on the metallogenic signature of post-subduction magmatism - David A. Holwell (Nature Portfolio, 2019)
Hydrous and alkali rich magmas rise through the lithosphere and may host gold-rich ore deposits – a poorly understood process. Here, the authors present new chalcophile element data across a metallogenic section of the lithosphere and suggest a continuous or staged ascent of magmatic-hydrothermal settings from mantle to upper crust.